Long‐term flavor recognition in humans with prenatal garlic experience. Issue 5 (2nd July 2012) - Hepper, Peter G.; Wells, Deborah L.; Dornan, James C.; Lynch, Catherine
Abstract The human fetus learns about its chemosensory environment and this influences its behavior at birth and during the nursing period. This study examined whether prenatal experience could influence behavior much later in life. The dietary preference of two groups of children (8‐ to 9‐years old) was examined. Mothers of one group had consumed garlic during pregnancy, mothers of the control group had not. Children received two tests, 1 month apart, of a meal containing two portions of potato gratin, one flavored with garlic. The total amount of potato, and the percentage of garlic flavored potato, eaten was calculated and examined separately by ANOVA for factors of prenatal exposure, the child's sex, and trial. Children prenatally exposed to garlic ate significantly more garlic flavored potato and a significantly greater overall amount of potato on trial 2, compared to controls. The results demonstrate prenatal experience may affect behavior well into childhood. © 2012 Wiley Periodicals, Inc. Dev Psychobiol 55: 568–574, 2013